2010
DOI: 10.1210/en.2010-0170
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Regulates Amiloride-Binding Protein 1 through CCAAT/Enhancer-Binding Protein-β in Mouse Uterus during Embryo Implantation and Decidualization

Abstract: Embryo implantation is an intricate interaction between receptive uterus and active blastocyst. The mechanism underlying embryo implantation is still unknown. Although histamine and putrescine are important for embryo implantation and decidualization, excess amount of histamine and putrescine is harmful. Amiloride binding protein 1 (Abp1) is a membrane-associated amine oxidase and mainly metabolizes histamine and putrescine. In this study, we first showed that Abp1 is strongly expressed in the decidua on d 5-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 38 publications
2
43
0
Order By: Relevance
“…A previous study found that cAMP levels significantly increased after sesame oil stimulation of the uterine horn (Rankin et al 1977). Moreover, cAMP could induce and regulate the decidualization of uterine stromal cells (Gellersen & Brosens 2003, Liang et al 2010. In mouse uterine stromal cells cultured in vitro, we found that cAMP induced the expression of the Cryab gene, which further supports a role for Cryab in decidualization.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…A previous study found that cAMP levels significantly increased after sesame oil stimulation of the uterine horn (Rankin et al 1977). Moreover, cAMP could induce and regulate the decidualization of uterine stromal cells (Gellersen & Brosens 2003, Liang et al 2010. In mouse uterine stromal cells cultured in vitro, we found that cAMP induced the expression of the Cryab gene, which further supports a role for Cryab in decidualization.…”
Section: Discussionsupporting
confidence: 80%
“…Uterine stromal cells were isolated as previously reported (Liang et al 2010). Briefly, uterine horns from day 4 pregnant mice were split longitudinally to expose the uterine lumen and digested in Hanks' balanced salt solution (HBSS) containing 1% trypsin (Amresco, Solon, OH, USA) and 6 mg/ml dispase (Roche).…”
Section: Isolation Of Uterine Stromal Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proximal AOC1 promoter * This work was supported by Deutsche Forschungsgemeinschaft Grant region is GC-rich and displays no TATA box, CAAT box, or consensus initiator sequence (16). Liang et al (26) reported that estrogen can induce AOC1 expression via CCAAT/enhancerbinding protein-␤ in mouse uterus during embryo implantation and decidualization. Other putative trans-acting factors include cyclic AMP, bone morphogenetic protein 2, and ERK1/2 (26).…”
mentioning
confidence: 99%
“…Liang et al (26) reported that estrogen can induce AOC1 expression via CCAAT/enhancerbinding protein-␤ in mouse uterus during embryo implantation and decidualization. Other putative trans-acting factors include cyclic AMP, bone morphogenetic protein 2, and ERK1/2 (26).…”
mentioning
confidence: 99%